Analisis Perbedaan Kinerja Saham Perusahaan Berdasarkan Model Sharpe, Treynor, Jensen dan Sortino Pada Kelompok Saham LQ 45 Di Bursa Efek Indonesia Periode 2010 – 2018 - Pantun Bukit; Yunan Surono; Nani Astriana (J-MAS (Jurnal Manajemen dan Sains), 2019)
The research aims to prove the difference in stock performance of LQ 45 stock group companies in the Indonesia Stock Exchange period 2010 – 2018 based on the models Sharpe, Treynor, Jensen and Sortino, and to get a group of stocks that have the most performance well based on the four models. In this research the samples used were the LQ 45 stock group in the Indonesia Stock Exchange from 2010 – 2018 which always emerged as the LQ 45 index counter of as many as 21 issuers, which provided complete data from financial statements, not including banking stocks because it has different financial statements, does not do stock split and does not have a negative book equity. This form of research is an explolanatoris research. The results showed that based on the value of figures with Sharpe model in the range-15.92764 to the maximum range of 25.85580. For model number values with model Treynor in the range-0.22986 to the maximum range of 0.37314. The value of the Jensen model number in the range-0.08787 to the maximum range is 0.33096., while the number value with the Sortino model at the range-5.86684 to the maximum range of 9.52381. Based on the measurement of the performance of groups with the Sharpe model has a minimal performance score with Z-score-2.88024 which occurred in July of 2013., while the maximum performance score with Z-score 4.36889 happened in August of 2018.  The Treynor model has a minimal performance score with Z-score – 2.88024 that occurred in July of 2013., while the maximum performance score with Z-score 4.36889 occurred in August of 2018. On the Jensen model had a minimal performance score with Z-score-1.99550 which occurred in July of 2013., while the maximum performance score with Z-score 7.30738 occurred in August of 2018. On the Sortino model had a minimal performance score with Z-score-2.88024 which took place in July of 2013., while the maximum performance score with Z-score 4.36889 occurred in August of 2018. The results of the test with Kruskal Wallish test on the four models acquired χ2 = 4.267, with a probability of 0.118. Then it can be known that the probability of testing > 0.05 and χ2 count < χ2 table 5.32. These results showed that there was no significant difference between testing with models of Sharpe, Treynor, Jensen and Sortino. Thus the nil hypothesis (H0) In this study was received. Another test by comparing the calculation of the stock group performance calculations as a continuation of the Kruskal Wallish test was obtained there is no meaningful difference between each treatment by looking at the difference to the four mean rank , which demonstrates consistency in the interdistinction between the four measurements.